ANALYSIS OF FOOD CONSUMPTION PATTERNS OF LOCAL PADDY FARMERS’ HOUSEHOLDS IN BARAMBAI DISTRICT OF BARITO KUALA REGENCY, INDONESIA - Ramadhani R.P.; Husaini M.; Hamdani (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
Food consumption patterns at the household level have become critical for analysis. In particular, in the recessed land with poor physical, biological and chemical conditions soil soil production and productivity produced peasants are very low. Peasant land is generally more cultivated local peas because it is able to adapt to the conditions of the land. Local usahani peas production generally is relatively low, resulting in income obtained is also low, so will affect the patterns of food consumption of farmers households. The study aims to analyze the food consumption patterns of local peanut farmers' households, and to analyse the factors that influence the food consumer pattern of the local peat farmer's household. Sampling was done using two-stage random sampling; the first stage of 11 villages in the district took randomly as much as 1 village, namely Pendalaman Village. The second stage numbered the population of peasant farmers in the village as 186 and took as many as 86 people sample with simple random sampling technique. The results show that the food consumption patterns of households of local peanut farmers are not as varied as the rice-peanut pattern. The consumption of carbohydrates is dominated by foods that come from peas and protein sources from fish, the average ACE farm households were 1,587,64>1,470 kcal/capita per day, so the entire household of peasants included a well-being. Food consumption expenditure factors, the number of ideal households and the productive life of the head of the family have a significant influence on the food-consumption patterns of local peasant farmers, while the education of head of family and mother of household has no significant impact.